PREVENTING STUNTING IN INFANTS AND TODDLERS MATTERS - Kartiko Kusumo Wardani, Dyah Woro; Ida Pratiwi, Agustina; Irawan, Yetty; Suhaid, Dewi Novitasari; Margaretha Manungkalit, Eviyani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Stunting or short stature is defined as a condition where the length or height has a z-score below -2SD based on growth standards, depending on age. Stunting can also be interpreted as a condition of children under the age of five who, due to chronic malnutrition (since the womb and in the first days after birth), develop stunted growth that does not appear until the age of 2 years. The most critical intervention to reduce stunt prevalence occurs in the first 1000 days of life in children under the age of five or before the age of 2, as children aged 2 to 3 experience a slowdown in growth and catch up with children's Growth opportunities at this age are lower than children aged 6 to 24 months. The prevalence of stunting is 19.7% in Central Jakarta, second only to North Jakarta. One of the actions that can be taken to prevent stunting is to provide information and education to mothers at Posyandu Dahlia in Paseban on the definition of stunting, effects, dangers, and how to prevent and correct stunting in children under the age of 2. With increasing knowledge one hopes to be able to prevent stunting. From the results of the pre- and post-tests conducted on 45 participants, there was an 83% increase in knowledge. This demonstrates that this health promotion intervention has succeeded in expanding knowledge and providing participants with knowledge benefits related to stunting.